Janus Carbon Nanotube Membranes by Selective Surface Plasmoxidation. Issue 18 (4th August 2016) - Abraham, Sinoj; Ma, Guibin; Montemagno, Carlo D.
Abstract : Janus membranes with superhydrophilic and superhydrophobic surfaces are developed using carbon nanotube mats by selective plasmoxidation and subsequent silanation. These membranes can separate stable oil–water emulsions and can withstand high temperature and pressure conditions with excellent chemical tolerance, thereby provide an economical solution for environmental remediation such as oil spill clean ups, waste water treatment, and oil recovery.